The New PI3K/mTOR Inhibitor GNE-477 Inhibits the Malignant Behavior of Human Glioblastoma Cells - Wang, Yixuan; Shen, Heng; Sun, Qian; Zhao, Linyao; Liu, Hao; Ye, Liguo; Xu, Yang; Cai, Jiayang; Li, Yuntao; Gao, Lun; Tan, Yinqiu; Liu, Baohui; et al. (Frontiers in Pharmacology, 2021)
The most common primary central nervous system tumor in adults is glioblastoma multiforme (GBM). The high invasiveness of GBM cells is an important factor leading to inevitable tumor recurrence and a poor prognosis of patients. GNE-477, a novel PI3K/mTOR inhibitor, has been reported to exert antiproliferative effects on other cancer cells. However, researchers have not clearly determined whether GNE-477 produces antitumor effects on GBM. In the present study, GNE-477 significantly inhibited the proliferation, migration and invasion of U87 and U251 cells. In addition, GNE-477 also induced apoptosis of GBM cells, arresting the cell cycle in G0/G1 phase. More importantly, GNE-477 also reduced the levels of AKT and mTOR phosphorylation in the AKT/mTOR signaling pathway in a concentration-dependent manner. An increase in AKT activity induced by SC79 rescued the GNE-477-mediated inhibition of GBM cell proliferation and apoptosis. The antitumor effects of GNE-477 and the regulatory effects on related molecules were further confirmed in vivo using a nude mouse intracranial xenograft model. In conclusion, our study indicated that GNE-477 exerted significant antitumor effects on GBM cells in vitro and in vivo by downregulating the AKT/mTOR pathway.